TRANSMISI HARGA KOPI ANTARA PASAR INDONESIA DENGAN PASAR TUJUAN EKSPOR UTAMA - Khumaira Khumaira; Dedi Budiman Hakim; Sahara Sahara (Jurnal Manajemen & Agribisnis, 2016)
Indonesia is the world’s fourth biggest coffee exporter with a market share of 9.7 %. This study examined the asymmetric price transmission in the coffee market between the importing countries (United State, German, and Japan) and Indonesia. AECM (Asymmetric Error Correction Model) was used to examine the asymmetric price transmission by using the monthly data from 2005 to 2014. The result of the study showed  that there is no price asymmetry in the coffee market in the long run because there is no market power in the coffee market; however,   in the short run, there is asymmetry price transmission in the United State and Japan due to the adjustment cost. Keywords: coffee, asymmetric price transmission, AECM